Management of Karate Extracurricular Programs in Developing Students' Non-Academic Achievements: A Comparative Case Study - Minah Minah; Dinny Mardiana (Journal of Innovation and Research in Primary Education, 2026)
Extracurricular activities play a crucial role in developing students' non-academic achievements, yet their management often remains suboptimal due to resource constraints and inadequate systematic approaches. This study examined how karate extracurricular programs are managed to support non-academic achievement development at two elementary schools in Jakarta, Indonesia. A qualitative case study design was employed at SDN Jembatan Besi 01 Pagi and SDN Kapuk 13 Petang from June to September 2025. Data were collected through in-depth interviews with principals, teachers, coaches, and students, participatory observations of training sessions, and document analysis. Miles and Huberman's interactive analysis model guided data analysis, while triangulation strategies ensured trustworthiness. Both schools implemented five management functions—planning, organizing, actuating, controlling, and follow-up—though with varying effectiveness. SDN Jembatan Besi 01 Pagi demonstrated more systematic planning documentation, balanced evaluation incorporating character development indicators, and proactive external partnerships. SDN Kapuk 13 Petang faced coach shortages and emphasized competition-focused evaluation. Both programs contributed to students' discipline, self-confidence, cooperation skills, and competitive achievements. Effective karate program management requires systematic application of management functions with contextual adaptation, balanced evaluation approaches, and stakeholder collaboration. Findings provide actionable guidance for enhancing extracurricular program quality in resource-constrained settings.